Job Hopping Intention of Millennial Employees - Grace Amin; Nur Intan Kinasih (FIRM Journal of Management Studies, 2022)
Job hopping is the phenomenon of employees who are changing jobs frequently in a short period of time as the result of their own decision, not by the dismissal of the organization. Many millennial employees believe they will not stay in their current organization for longer than three years. Thus, it becomes an urgent problem since millennials will be the larger generation who occupy the workplace in 2020 that will replace the baby boomers generation who will retire from their current position in organizations. This research intends to find out the influence of four independent variables: job motivation, job satisfaction, psychological contract, and person-environment fit towards one dependent variable: job-hopping intention. This research is conducted using a quantitative method with multiple regression analysis to determine the significant relationship between variables. The population of this research was millennial employees in the Jakarta area. There were 150 participants who filled out the questionnaire. This research found there is a negative influence on job motivation and job satisfaction towards job-hopping intention, while the psychological contract and person-environmental fit have no significant influence on job-hopping intention. All the independent variables contribute 59.3% towards millennial job-hopping intention in the Jakarta area